2020
DOI: 10.1111/pedi.13086
|View full text |Cite
|
Sign up to set email alerts
|

Increased tissue factor activity promotes thrombin generation at type 1 diabetes onset in children

Abstract: Objective: In type 1 diabetes (T1D), a prothrombotic status due to elevated coagulation factors coincides with metabolic derailment. In a previous study, we discovered altered thrombin generation profiles in children with T1D. These alterations are potentially most pronounced at T1D onset and ameliorated after insulin treatment. We tested this hypothesis in a longitudinal study, measuring thrombin generation together with coagulation parameters in children at T1D onset and during follow-up. Materials and metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…This is of particular interest, as people with diabetes are already at increased risk of thromboembolic events. [ 7 , 19 , 20 ]…”
Section: Discussionmentioning
confidence: 99%
“…This is of particular interest, as people with diabetes are already at increased risk of thromboembolic events. [ 7 , 19 , 20 ]…”
Section: Discussionmentioning
confidence: 99%
“…Although TF is expressed in various cells, tissue inflammation enhances its expression in tissue macrophages [ 6 ]. On the other hand, diabetic and inflammatory states have been shown to increase blood TF levels despite almost undetectable blood TF levels in the physiological state [ 6 , 18 20 ]. The present study showed that the diabetic state increased plasma TF levels in mice, but did not affect TF expression in bone tissues, and also that femoral bone injury did not affect the expression of TF in injured sites.…”
Section: Discussionmentioning
confidence: 99%
“…We previously revealed the involvement of PAI-1 in delayed bone repair induced by a diabetic state in mice [ 15 17 ]. TF antigen levels and the number of TF-positive microvesicles were found to be elevated in the blood of diabetic patients [ 18 , 19 ]. However, it is important to note that several methods may be used to measure plasma TF levels, including antigen- and activity-based assays [ 20 ].…”
Section: Introductionmentioning
confidence: 99%